Mindfulness and academic procrastination among Chinese adolescents: a moderated mediation model - Yue, Pengfei; Zhang, Jiaxin; Jing, Yumei (Frontiers in Psychology, 2024)
Background ： While previous studies have linked mindfulness to reduced academic procrastination, the mechanisms involved remain under-explored. This study deepens the understanding by investigating how learning vigor mediates the mindfulness and procrastination relationship, and how harsh parenting influences this mediation.This study, adopting a positivist research approach, utilized a cross-sectional design. Data were collected from 800 students at three middle schools in Henan Province, China, through cluster random sampling. This approach yielded 800 questionnaires. The participants sequentially completed four questionnaires: the Mindfulness Attention Awareness Scale, the Utrecht Work Engagement Scale-Student, the Aitken Procrastination Inventory, and the Harsh Parenting Questionnaire. After removing 67 invalid questionnaires due to incomplete responses and patterned answers, a total of 733 valid questionnaires were obtained, with 53.3% girls and an average age of 13.12 years (SD = 1.01), leading to an effectiveness rate of 91.63%. Upon data collection, SPSS 26.0 software was used for correlation analysis, mediation analysis, and moderated mediation analysis to assess the relationships between variables.(2)Learning vigor serves as a mediator in the relationship between mindfulness and academic procrastination; and(3)Harsh parenting moderates the relationship between mindfulness and learning vigor. Specifically, the positive impact of mindfulness on learning vigor is more pronounced in individuals experiencing lower levels of harsh parenting compared to those with higher levels.This study reveals that mindfulness significantly protects against academic procrastination in adolescents, with 52.27% of this effect mediated by increased learning vigor. Additionally, it shows that high levels of harsh parenting weaken mindfulness's positive impact on learning vigor, tempering its overall protective influence on procrastination. These insights, which apply Trait Activation Theory to educational psychology, not only deepen our understanding of the dynamics between mindfulness and procrastination but also have important implications for addressing academic procrastination in Chinese adolescents.